Species Diversity and Food Potential of Orangutans in Genting Tanah Village Forest - Suparjo, Suparjo; Suwasono, Raharjo Ari; Lasmito, Lasmito; Suyitno, Agus; Atut, Yohanes (P3KM Politeknik Pertanian Negeri Samarinda, 2024)
The aim of the research is to determine the diversity of vegetation in the forests of Genting Tanah Village which has the potential to feed orangutans (Pongo pygmaeus morio). The research method is an inventory of sample plots. Data were analyzed quantitatively by calculating the Relative Density, Relative Frequency, Relative Dominance and Diversity Index values. The choice of orangutan food is determined by comparing it based on literature regarding orangutan food. The research identified 67 types of vegetation belonging to 44 families. At tree level there are 20 types of vegetation, with Shorea teysmanniana Dyer being the most important with an Importance Value Index of 78.06%. At pole level there are 32 species, with Combretocarpus rotundatus Miq. has the highest Important Value Index of 74.43%. Genting Tanah village forest also has 40 species of saplings and 41 species of undergrowth. Mallotus muticus Mull. has the highest Importance Value Index of 55.78% in the sapling group, while Hypolytrum nemorum Vahl has the highest Importance Value Index of 21.24% in the seedling and undergrowth group. The species diversity index at the seedling level of 3.24 is considered high, while the species richness index is low at the tree level and moderate at the pole level. Based on the 67 species identified, there are 34 species that have the potential to be a source of orangutan’s food.